Resisting Modernism or the Last Gasp of the Arts and Crafts?: Church Building in Canterbury and North Otago in the ’Thirties - Lochhead, Ian (Architectural History Aotearoa, 2006)
The dominant historical narratives of twentieth-century architecture present the 1930s as the period during which Modernism’s claim to be the architectural style of the century was consolidated and when the new architecture began to spread across the globe. In New Zealand, as in the rest of the world, this master narrative has tended to obscure the significance of buildings constructed in more traditional styles. The five New Zealand buildings included in the RIBA’s Centennial Exhibition, International Architecture 1924-1934, were not, however, the latest examples of Modernism in this country, but relatively conservative designs, including Cecil Wood’s Arts and Crafts inspired St Barnabas’s Church at Woodend (1932). Wood’s building forms part of an extensive group of small country churches built throughout Canterbury and North Otago during the ’thirties. These include Wood’s St Paul’s, Tai Tapu (1930-31) and Herbert Hall’s St David’s Memorial Church at Cave (1930), although by far the best know is RSD Harman’s Church of the Good Shepherd at Lake Tekapo (1935). These small, unpretentious churches, many built with assistance from a government fund initiated to stimulate the construction industry, made use of modern materials, especially reinforced concrete, but their mode of expression remained conservative. They were often embellished with furnishings executed in the traditions of the Arts and Crafts movement. In most cases these churches were important statements of local identity while at the same time expressing the diverse cultural origins of those who built them. In style they were invariably Gothic yet within that dominant idiom considerable stylistic diversity was achieved. For both architects and their clients Modernism, with its emphasis on internationalism and the machine, was unable to express the rich veins of meaning which such buildings were required to embody. Yet as expressions of the uncertainties of the time, their conservative aesthetic values, their reassertion of pioneering roots and of an enduring local identity were as significant as Modernism’s confident assertion of a better, essentially urban, future. At a time when the approaching Centennial events of 1940 was stimulating a reassessment of the country’s past, these buildings also acted as powerful statements of consolidated achievements.